TANGGAPAN RESPONDEN MENGENAI MEDIA PEMBELAJARAN "VIRTUAL MOJI LEARNING" - Rabbani, Ilham; Arianingsih, Anisa (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2023)
The purpose of this study is to find out respondents respond about the Virtual Moji Learning learning media. The research method used is the Multimedia Development Life Cycle (MDLC) method. The process stages that will be carried out are conceptualization, design, collection of materials, manufacture, testing and distribution. This research was conducted online and involved 30 students of the 1st level Japanese Literature study program at the Universitas Komputer Indonesia. The method used in data collection is a questionnaire that is distributed online and the results will be calculated using a Likert scale. The results of this study indicate that the Virtual Moji Learning obtains a percentage value of 84.6% on the ideal percentage count, so it can be concluded that the Virtual Moji Learning video is suitable for use in the kanji N5 learning media. Keywords: Online Learning, Learning Media, Kanji